2012
DOI: 10.1371/journal.pone.0050057
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of the High Molecular Weight Glutenin Subunit 1Ax1 and Puroindoline Improves Dough Mixing Properties in Durum Wheat (Triticum turgidum L. ssp. durum)

Abstract: Wheat end-use quality mainly derives from two interrelated characteristics: the compositions of gluten proteins and grain hardness. The composition of gluten proteins determines dough rheological properties and thus confers the unique viscoelastic property on dough. One group of gluten proteins, high molecular weight glutenin subunits (HMW-GS), plays an important role in dough functional properties. On the other hand, grain hardness, which influences the milling process of flour, is controlled by Puroindoline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Relationships between Mixograph parameters and dough viscoelasticity have been studied in details [40] and associations of these parameters with other wheat quality traits were also discussed previously [43]. In general, MPW and MRW positively correlated with dough resistance to extension [21], whereas WS and MTxW negatively and positively correlated with tolerance to over-mixing, respectively [40], [44], [45]. Parameters of the curve height values (MLV, MPV, MRV and MTxV) positively correlated with dough elasticity [39].…”
Section: Discussionmentioning
confidence: 98%
“…Relationships between Mixograph parameters and dough viscoelasticity have been studied in details [40] and associations of these parameters with other wheat quality traits were also discussed previously [43]. In general, MPW and MRW positively correlated with dough resistance to extension [21], whereas WS and MTxW negatively and positively correlated with tolerance to over-mixing, respectively [40], [44], [45]. Parameters of the curve height values (MLV, MPV, MRV and MTxV) positively correlated with dough elasticity [39].…”
Section: Discussionmentioning
confidence: 98%
“…7). However, co-expression of TaGlu-Ax1 and PINA in durum wheat is increased dough strength and resistance to extension than lines expressing TaGlu-Ax1 or Pina [19].…”
Section: Discussionmentioning
confidence: 92%
“…Although co-expression of TaGlu-Ax1 and PINA in durum wheat have combined effects on dough mixing behaviors with a better dough strength and resistance to extension than those from lines expressing TaGlu-Ax1 or Pina [19], the expression of TaGlu-Ax1 is no doubt to influence the processing properties. Overexpression of HMW-GS Ax1 in several durum wheat cultivars resulted in increased dough strength [13].…”
Section: Introductionmentioning
confidence: 99%
“…Improving quality characteristics is one of the primary concerns when developing commercial varieties suitable for human and animal consumption. For example, grain protein content, protein quality, flour color, and grain texture are key quality criteria when developing wheat varieties for bread and pasta production (Sissons, 2008). …”
Section: Applications Of Pentaploid Wheat Hybridsmentioning
confidence: 99%
“…Interspecific hybridisation involving hexaploid/tetraploid crosses has demonstrated that the resultant progeny have significantly improved grain weight, grain diameter, and grain yield (Kalous et al, 2015). Furthermore, it was suggested that introducing 1D chromosome segments and their associated protein products would improve the bread making quality of durum wheat (Sissons, 2008). Wang et al (2005) indicated that recombinant allohexaploid lines, which had retained all seven copies of the D genome chromosomes, had enhanced protein content compared to their hexaploid parental lines.…”
Section: Applications Of Pentaploid Wheat Hybridsmentioning
confidence: 99%